2014
DOI: 10.1097/ccm.0000000000000524
|View full text |Cite
|
Sign up to set email alerts
|

Lung-Targeted RNA Interference Against Angiopoietin-2 Ameliorates Multiple Organ Dysfunction and Death in Sepsis

Abstract: The Tie2 antagonist angiopoietin-2 represents a promising target against sepsis-associated multiple organ dysfunction. A novel RNA interference therapeutic approach targeting gene expression in the pulmonary endothelium could be a clinically relevant pharmacological strategy to reduce injurious angiopoietin-2 synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 34 publications
3
50
0
Order By: Relevance
“…Prolonged elevations in Angpt2 levels in patients are associated with a higher rate of MOF and poor prognosis (4). Recent studies have identified Angpt2 as a potential mediator of MOF in sepsis and ARDS (4,19,33,41). However, the role of Angpt2 in remote organ injury due to VILI has not been previously described.…”
Section: Discussionmentioning
confidence: 95%
“…Prolonged elevations in Angpt2 levels in patients are associated with a higher rate of MOF and poor prognosis (4). Recent studies have identified Angpt2 as a potential mediator of MOF in sepsis and ARDS (4,19,33,41). However, the role of Angpt2 in remote organ injury due to VILI has not been previously described.…”
Section: Discussionmentioning
confidence: 95%
“…Recombinant ANG1, inhibition of ANG2 or increasing Tie2 activity by therapeutic antibodies or a small-molecule phosphatase inhibitor have vascular protective effects in acute inflammation and in sepsis (32,33,34,62,72,73), consistent with an agonist action of ANG1 and antagonistic action of ANG2. Reduced Tie2 protein and Tie2 and Ang1 mRNA levels have been reported in murine sepsis and systemic inflammation (56,74).…”
Section: Methodsmentioning
confidence: 97%
“…enhances Tie2 activation and counteracts leakage (1,6,(15)(16)(17). The role of TIE2 gene expression has not been fully investigated in this and related settings.…”
Section: Significancementioning
confidence: 99%